Factor Market Failures and the Adoption of Irrigation in Rwanda - Jones, Maria Ruth (World Bank, Washington, DC, 2019)
This paper examines constraints to adoption of new technologies in the context of hillside irrigation schemes in Rwanda. It leverages a plot-level spatial regression discontinuity design to produce 3 key results. First, irrigation enables dry season horticultural production, which boosts on-farm cash profits by 70 percent. Second, adoption is constrained: access to irrigation causes farmers to substitute labor and inputs away from their other plots. Eliminating this substitution would increase adoption by at least 21 percent. Third, this substitution is largest for smaller households and wealthier households. This result can be explained by labor market failures in a standard agricultural household model.